2018
DOI: 10.3390/ma11060868
|View full text |Cite
|
Sign up to set email alerts
|

Fully Ab-Initio Determination of the Thermoelectric Properties of Half-Heusler NiTiSn: Crucial Role of Interstitial Ni Defects

Abstract: For thermoelectric applications, ab initio methods generally fail to predict the transport properties of the materials because of their inability to predict properly the carrier concentrations that control the electronic properties. In this work, a methodology to fill in this gap is applied on the NiTiSn half Heusler phase. For that, we show that the main defects act as donor of electrons and are responsible of the electronic properties of the material. Indeed, the presence of Nii interstitial defects explains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…We observe that at temperatures below room temperature, the ZT value varies from 0.75 to 0.99 for Ba 2 LuTa 0.75 TM 0.25 O 6 materials. Thus, in comparison with other values of the figure of merit at room temperature reported in previous theoretical and experimental studies, such as NiTiSn [ 68 ] and CuI–Pb co‐doped Bi 2 Te 3 ( ZT = 0.96), [ 69 ] it can be concluded that this material can be regarded as a suitable material for application in the thermoelectric cooling industry.…”
Section: Resultssupporting
confidence: 70%
“…We observe that at temperatures below room temperature, the ZT value varies from 0.75 to 0.99 for Ba 2 LuTa 0.75 TM 0.25 O 6 materials. Thus, in comparison with other values of the figure of merit at room temperature reported in previous theoretical and experimental studies, such as NiTiSn [ 68 ] and CuI–Pb co‐doped Bi 2 Te 3 ( ZT = 0.96), [ 69 ] it can be concluded that this material can be regarded as a suitable material for application in the thermoelectric cooling industry.…”
Section: Resultssupporting
confidence: 70%
“…In this half‐Heusler material, Ni plays a unique role in either phonon or electron transport. Based on first‐principle calculations, interstitial Ni atoms are energetically more favorable than other types of defects . Neutron diffraction results have also confirmed partial occupancy of the 4d position by a small amount of Ni in the 1:1:1 stoichiometric TiNiSn …”
Section: Introductionmentioning
confidence: 90%
“…It has been speculated that slight change in alloy composition in the experimental samples due to point defects may explain this deviation from the usual trend observed in semiconductors [57,64,65]. While external doping is the commonly employed point defect engineering strategy for tailoring carrier concentration and mobility [44][45][46][88][89][90][91][92][93][94], intrinsic point defects can also modify electronic structure, carrier concentration, and hence transport properties of half-Heusler alloys [95][96][97][98][99][100][101][102]. The high-resolution angle-resolved photoemission spectroscopy (ARPES) measurements can be used to gain insights into the defect-induced changes in the electronic structure [99,103].…”
Section: B Electronic Band Structure and Density Of Statesmentioning
confidence: 99%